On comparisons of random, partition, and proportional partition testing. - Ntafos, S.C.
Early studies of random versus partition testing used the probability of detecting at least one failure as a measure of test effectiveness and indicated that partition testing is not significantly more effective than random testing. More recent studies have focused on proportional partition testing because a proportional allocation of the test cases (according to the probabilities of the subdomains) can guarantee that partition testing will perform at least as well as random testing. We show that this goal for partition testing is not a worthwhile one. Guaranteeing that partition testing has at least as high a probability of detecting a failure comes at the expense of decreasing its relative advantage over random testing. We then discuss other problems with previous studies and show that failure to include important factors (cost, relative effectiveness) can lead to misleading results
Keywords: Partition testing; Probability; Program testing; Proportional partition testing; Random testing; Software failure detection; Software reliability; Test cases; Test effectiveness